The economics of tourism / Dr. Muhammad Hanif Othman and Zouhair Mohd Rosli - Othman, Muhammad Hanif; Mohd Rosli, Zouhair (Universiti Teknologi MARA, Kedah, 2024)
Tourism economics involves the allocation of scarce resources to meet the tourism demand. On the supply side, tourism encompasses a variety of goods and services, including travel agency services, food and beverages, accommodation, transport and logistics, and retail goods (Mohd Rosli, 2022; Department of Statistics Malaysia, 2022; Othman, 2019). Tourism demand can manifest in different forms, such as from groups of countries, states, regions, or specific areas. Additionally, it can be categorised by visits or tourists and extend to specific products like attractions, accommodation, sightseeing, sports, and transportation (Tourism Malaysia, 2020). Malaysia's Tourism Satellite Account (TSA) classifies visitors into tourists (i.e., those with overnight stays) and excursionists (i.e., individuals with trips lasting less than 24 hours) (Department of Statistics Malaysia, 2022). According to TSA, the primary purposes for visits include: 1. Business and professionals 2. Holiday, recreation, and leisure 3. Visiting friends and relatives 4. Education and training 5. Medical healthcare 6. Religion purposes or pilgrimage 7. Shopping 8. Transit Tourism expenditures also consist of various categories: 1. Inbound tourism expenditure: Tourism expenditures of a non-resident tourist within the economy of reference. 2. Domestic tourism expenditure: Tourism expenditures of a resident tourist within the economy of reference. 3. Outbound tourism expenditure: Tourism expenditures of a resident tourist outside the economy of reference. 4. Internal tourism consumption: Comprises all tourism expenditure of tourists, both resident and non-resident, within the economy of reference. In other words, it combines inbound and domestic tourism expenditures. Many studies considered tourism demand at the national level, either through tourist arrivals, departures, expenditures, and length of stay (Mohd Rosli, 2022; Othman, 2019). Determinants of tourism demand are primarily tourists’ income, relative price between the origin and destination or cross-price difference, exchange rate, travel costs, and political stability (Puah et al., 2019; Shafiullah et al., 2019; Ibragimov et al., 2021). Higher tourists’ income, lower price level of the destination country, stronger exchange rate, and lower travel costs entice foreign tourists to visit the country. Nevertheless, political instability discourages inbound tourism activities.